Is thiazolidinediones use a factor in delaying the need for insulin therapy in type 2 patients with diabetes? A population-based cohort study. Issue 6 (12th November 2012) - Carney, Greg A; Bassett, Ken; Wright, James M; Dormuth, Colin R
Abstract : Objective: To understand the independent role of thiazolidinediones (TZDs) in delaying progression to parenteral insulin therapy. Design: Population-based retrospective cohort study. Setting: British Columbia, Canada. Participants: A total of 18 867 type 2 diabetes patients (mean age 58.9) treated with metformin as first-line therapy who then switched or added a TZD or sulphonylurea as a second-line treatment between 1 January 1998 and 31 March 2008. Outcome measures: Multivariable Poisson regression models were used to estimate the effect of using TZD compared to sulphonylureas on time to the initiation of insulin treatment (third-line). Results: The adjusted rate difference in women aged <60 showed 2.22 fewer insulin initiation events per 100 person-years (PYs) in the TZD group versus the sulphonylurea group (95% CI −3.46 to −0.99). Men in the same age group had 1.50 fewer insulin initiation events per 100 PYs in the TZD group versus the sulphonylurea group (95% CI −2.44 to −0.56). The average time in days to initiation on insulin in the sulphonylurea, rosiglitazone and pioglitazone group was 343, 252 and 339, respectively. The cumulative hazard for starting insulin for sulphonylurea patients at 12, 24, 36 and 48 months was approximately three times higher compared to TZD patients. Conclusions: Second-line TZD therapy compared to second-line sulphonylurea therapy was associated with a lower incidence of insulin initiation as third-line treatment in patients with type 2 diabetes, with a mean delay of 90 days. This duration of delay must be weighed against the absence of a proven reduction in morbidity or mortality with TZDs and their known serious cardiovascular harm.